General biochemical and immunological characterization of the venom from the scorpion Tityus trivittatus of Argentina - de Roodt, Adolfo R. (2010)
Fil: de Roodt, Adolfo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos. Área Investigación y Desarrollo / Serpentario; Argentina.